An investigation of flumazenil to antagonize gamma-hydroxybutyrate intoxication in a murine model - Lee, David C. (Springer-Verlag, 2006)
OBJECTIVE: Prior animal studies have suggested that flumazenil may blunt GHB’s sedative-hypnotic affects. We hypothesized that flumazenil would decrease the affects of GHB in a murine model of intoxication. METHODS: We performed a controlled, pilot experiment using 32 mice divided into 3 groups. All mice received intraperitoneal injections of GHB (1.5 g/kg). Group I received sham injections at time 0, and then GHB at 5 minutes. Group II received flumazenil (0.3 mg/kg) at time 0, and then GHB at 5 minutes. Group III received sham injection at time 0, then GHB at 5 minutes, and then 4 escalating flumazenil doses administered at 3-minute intervals (0.003 to 1 mg/kg). We measured certain functions: time to loss/recovery of righting reflexes (RR), time to sprawl/recovery of sprawl (postural tone [PT]), and death. RESULTS: There were statistically significant delays in the loss of PT and shortened recovery time to RR in pre-treated mice (group II) versus controls (group I). There were no differences in group III versus group I for any outcome parameters. CONCLUSIONS: In this model, pre-dosing flumazenil prior to GHB administration delayed clinical intoxication.